(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The Russian leasing market is increasingly growing and getting a profitable and common tool for funding the renewal of enterprises’ non-current assets. The competition level is getting particularly high, permitting the growth of that market and generating a heightened economic focus. Numerous issues and distinctions related to the appearance of a leasing tool in the Russian federation are made. Asa consequence, this study mainly seeks to analyze and discover the characteristics and issues of the Russian leasing market. To attain that aim, the study utilizes the approaches of bibliographic analysis and materials’ generalization on the research subject; classifications of factological material demonstrating the main elements of leasing expansion; the tools of economic, institutional, statistical, and structural analysis to set up the relations between the fundamental features of leasing. Given the results, leasing in the Russian federation attempts to cover a vast set of market segments, implying that companies are able to lease nearly every piece of equipment. In the leasing market in the Russian Federation, companies encounter several issues and dilemmas, the dominant of which are intense competition and heightened market concentration. However, the market persists in operating, and competition, to an extent, gets a major element in the market development.